Transcriptome and protein interaction profiling in cancer cells with mutations in histone H3.3 - Lim, Jinyeong; Baude, Annika; Fellenberg, Jörg (Scientific data, 2018)
Design Type(s) transcription profiling design • protein interaction analysis objective Measurement Type(s) protein expression profiling • transcription profiling by high throughput sequencing • transcription profiling by array assay Technology Type(s) liquid chromatography-tandem mass spectrometry • RNA sequencing Factor Type(s) age • biological sex Sample Characteristic(s) Homo sapiens • HEK-293 cell Machine-accessible metadata file describing the reported data (ISA-Tab format)